The determinants of efficiency and productivity in European railways - António Couto (2009)
This article evaluates the economic performance of European railways over the period 1972 to 1999. The cost structure of the railway industry is analysed using a stochastic frontier approach estimated within the framework of a translog cost system. The results confirm that European railways experience significant cost increases due to inefficient behaviour. In contrast to previous studies, however, the estimates indicate a much greater role for allocative rather than technical inefficiency. Overall, inefficiencies can essentially be explained by the supply of excess capacity and by the over-employment of labour inputs. Regarding productivity, it appears to be technological progress, and not levels of efficiency or scale economies, that provide the most convincing explanation for variance in growth rates within the sample.